Assessment of depression and anxiety in hematological cancer patients and their relationship with quality of life. - Das, Priscilla; Awang, Hamidin; Md. Zain, Azhar; Naing @ Noor Jan, Khin Ohnmar; Md Said, Salmiah; Khalid, Bahariah (2011)
OBJECTIVES:To determine the relationship between major depressive disorder, anxiety disorders and the quality of life of haematological cancer patients. METHODS: This cross-sectional study was conducted at Ampang Hospital Kuala Lumpur, Malaysia, a tertiary referral centre hospital for haematological cancer. The Mini-International Neuropsychiatric Interview was used for the diagnosis of major depressive disorder and anxiety disorders. The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire was utilised to measure patients' quality of life. RESULTS: A total of 105 haematological cancer patients were included in the study with response rate of 100%. Major depressive disorder correlated with almost all domains of the quality of life, except the pain scores. Logistic regression showed that insomnia and financial difficulties were related to major depressive disorder. Different anxiety disorders also correlated with quality of life in specific domains. The leading anxiety disorders that correlated mostly with quality-of-life scales were generalised anxiety disorder, followed by obsessive-compulsive disorder, social anxiety disorder, as well as post-traumatic stress disorder and panic disorder with agoraphobia (p<0.05). CONCLUSIONS: Psychological treatment along with medication and intervention should be implemented to improve the overall quality of life and psychiatric disorder symptoms among the haematological cancer patients.